PECULIARITIES OF RUNNING GEAR CONSTRUCTION OF ROLLING STOCK - Myamlin, S. V.; Lunys, O.; Neduzha, L. O. (Science and Transport Progress, 2017)
Purpose. To determine the dynamic qualities of the main locomotives that characterize safety traffic along straight and curved track sections in the entire range of operational speeds, it is necessary to perform a whole range of studies. One of the necessary conditions for a qualitative improvement of the traction rolling stock of railways is the determination of the parameters of its running gears. Among the issues related to this problem, the important task is to determine the dynamic qualities of locomotives at the design stage, taking into account the selected technical solutions in the design of running gears. At the same time, special attention is paid to the connections of the body with bogie, in particular, using the inclined rods. Methodology. Mathematical modeling is carried out by the method of numerical integration of the equations of the mathematical model of locomotive spatial oscillations to determine the dynamic loading of the mainline locomotive using the software package "Dynamics of Rail Vihicles" ("DYNRAIL"). Findings. The research results show that in order to create a simple and reliable design of running gears, which will reduce maintenance and repair costs, will have low initial cost and operating costs for the whole life cycle, high traction force as close as possible to the ultimate force in traction, will make it possible to operate in the multiple traction mode, the designers and scientists should implement scientific and technical solutions. Originality. In accordance with researches authors formed general classification formation of body/bogie connections and the general classification of structures of inclined rod of locomotives. Practical value. Generalization of the results of theoretical, scientific-methodical, experimental studies aimed at further improving the running gears of long-distance locomotives of perspective structures is urgent in improving the rolling stock constructions. The research carried out by the authors concerning improvement of the structural features of the running gear elements of some types for modern mainline locomotives are of practical value and can be used in the development of traction rolling stock.